An energy saving approach for rough milling tool path planning. Issue 2 (3rd March 2016) - Xu, Ke; Tang, Kai
Abstract: For a specific machine configuration, energy consumption in a rough milling process is strongly affected by three parameters: axial depth of cut, radial depth of cut and feed rate. On the other hand, feed rate is also physically constrained by a critical cutting force value. Based on these concerns, we establish an energy consumption formula as a function of the three, aiming to find out the optimal set of parameters which is the most energy-efficient. After that, two strategies, i.e. improved constant Z-level strategy and optimized morphing strategy for tool path generation in terms of 3-axis ball-end milling are thus presented based on the previous obtained parameters. Simulation show that the optimal parameters together with the proposed tool path generation methods can save up to 30% of the total energy usage compared with traditional cutting parameters in rough milling. GRAPHICAL ABSTRACT: